Answer:
(x, y, z) = (4, -1, 3)
Step-by-step explanation:
To solve the system of equations:
2x − 3y + 4z = 23 .........................(1)
x + 2y − 4z = −10 ..........................(2)
3x − y + 2z = 19..............................(3)
Simultaneously, we do that by first eliminating one variable from any two equations to have an equation in two variables. The process is repeated with one of the used equations and the third unused equation to have a second equation in two variables. The two equations in two variables obtained can then be easily solved simultaneously.
Let us eliminate z from (1) and (2)
Add (1) and (2)
(1) + (2):
3x - y = 13 ........................................(4)
Multiply (3) by 2
(3) × 2
6x - 2y + 4z = 38 ............................(5)
Add (5) and (2)
(5) + (2):
7x + 0 + 0 = 28
x = 28/7 = 4
Putting this in (4)
3(4) - y = 13
y = 12 - 13 = -1
Putting this in (3)
3(4) - 4(-1) + z = 19
z = 19 - 16 = 3
Therefore,
(x, y, z) = (4. -1, 3)